Lettuce mosaic virus: from pathogen diversity to host interactors - GERMAN‐RETANA, SYLVIE (Mol Plant Pathol, 2007)
Taxonomy:  Lettuce mosaic virus (LMV) belongs to the genus Potyvirus (type species Potato virus Y) in the family Potyviridae. Physical properties:  The virion is filamentous, flexuous with a length of 750 nm and a width of 15 nm. The particles are made of a genomic RNA of 10 080 nucleotides, covalently linked to a viral‐encoded protein (the VPg) at the 5′ end and with a 3′ poly A tail, and encapsidated in a single type of capsid protein. The molecular weight of the capsid protein subunit has been estimated electrophoretically to be 34 kDa and estimated from the amino acid sequence to be 31 kDa. Genome organization:  The genome is expressed as a polyprotein of 3255 amino‐acid residues, processed by three virus‐specific proteinases into ten mature proteins. Hosts:  LMV has a worldwide distribution and a relatively broad host range among several families. Weeds and ornamentals can act as local reservoirs for lettuce crops. In particular, many species within the family Asteraceae are susceptible to LMV, including cultivated and ornamental species such as common (Lactuca sativa), prickly (L. serriola) or wild (L. virosa) lettuce, endive/escarole (Cichorium endiva), safflower (Carthamus tinctorius), starthistle (Centaurea solstitialis), Cape daisy (Osteospermum spp.) and gazania (Gazania rigens). In addition, several species within the families Brassicaceae, Cucurbitaceae, Fabaceae, Solanaceae and Chenopodiaceae are natural or experimental hosts of LMV. Genetic control of resistance to LMV:  The only resistance genes currently used to protect lettuce crops worldwide are the recessive genes mo1 (1) and mo1 (2) corresponding to mutant alleles of the gene encoding the translation initiation factor eIF4E in lettuce. It is believed that at least one intact copy of eIF4E must be present to ensure virus accumulation. Transmission:  LMV is transmitted in a non‐persistent manner by a high number of aphid species. Myzus persicae and Macrosiphum euphorbiae are particularly active in disseminating this virus in the fields. LMV is also seedborne in lettuce. The effectiveness of LMV transmission depends on the cultivar and the age of the seed carrier at the inoculation time. Symptoms:  The characteristic symptoms on susceptible lettuce cultivars are dwarfism, mosaic, distortion and yellowing of the leaves with sometimes a much reduced heart of lettuce (failure to form heads). The differences in virus strains, cultivars and the physiological stage of the host at the moment of the attack cause different symptom severity: from a very slight discoloration of the veins to severe necrosis leading to the death of the plant.